Reconstituer l’environnement des entreprises : des parties prenantes aux actants parties prenantes ? L’exemple de la station touristique d’Essaouira - Nabil Ouarsafi; Khalid El Housni; Khalid Sadiqi (Études Caribéennes)
The theory of Stakeholders, “Stakeholder Theory” made stakeholder identification the central theme of its work. Despite multiple approaches, unanimity has not been reached on the actors considered as stakeholders, restricted only to the actors influencing economic performance. Given the importance of adopting a more inclusive approach, some authors have called for experimentation with other theoretical frameworks, even from other disciplines. The objective of this contribution is to test the capacity of the sociological theory of the actor-network in the identification of a wider network of stakeholders. This approach has been carried out in the tourist field of Essaouira in view of the large number of relationships that are established between its actors and has led to the new concept of "Actants-Stakeholders".